Interactions Between Systemic Inflammation, Frailty And Neuroinflammation In Ageing And Neurodegeneration - Healy, Daire (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2022)
Compelling evidence continues to define the pivotal role which inflammation plays in the progression of neurodegenerative diseases and ageing. It has emerged that inflammation outside the brain significantly contributes to inflammatory and degenerative changes inside the brain at least partly via alteration of the properties of microglial cells, the key brain immune cell population. Age-associated low-grade inflammation may contribute to brain aging but varies significantly among individuals, consistent with the idea that chronological ageing has limited predictive power for brain ageing. The main hypothesis pursued in this thesis is that frailty, a state of increased vulnerability due to the accumulation of multiple deficits in physiological systems, may contribute to the development of neuroinflammation. We have demonstrated robust regional differences in innate immune transcriptional signature across the ageing brain as well as evidence for ubiquitous microglial across all assessed regions. Novel physiological and cognitive frailty indices were designed to capture different aspects of the pathology of ageing, including metabolism, physiological condition and cognitive status. The research herein assessed the degree with which they, as individual components, contribute to the frailty of an individual as well as how this cumulative frailty status informs on the brain s vulnerability to, and recovery from, an acute stressor and found frailty and metabolism to be inextricably linked. The data showed that frailty status in ageing mice at the physiological, cognitive and molecular levels is strongly correlated with inflammatory and metabolic indicators in the blood and in discrete brain regions and structures. Following this characterisation of relationships between frailty and brain inflammation/integrity I have demonstrated the ability of repeated episodic systemic inflammation to exacerbate neuroinflammation and cognitive function. Using fluorescence activated cell sorting I isolated and assessed molecular indices of inflammation and glial activation and demonstrated evidence of microglial and astrocytic priming in response to amyloid pathology and repeated episodic systemic inflammation. A generally increased susceptibility of females in APP/PS1 pathology to cognitive and physiological impairment was observed here. These data suggest that across the lifespan age more strongly predicts microgliosis, but that within tighter age brackets, frailty adds to the neuroinflammatory status. The extent to which this increases an individual s vulnerability and susceptibility to secondary inflammatory insults has implications for our understanding of the interrelationship of frailty and dementia and remains the subject of further study.
APPROVED
Keywords: Frailty; Ageing; Neuroinflammation; Systemic inflammation; Microglia; Priming; Cognitive dysfunction; Delirium; Dementia; Alzheimer's